Keep thinking about unanswered questions in primary care: Cultivating negative capability - Daisuke Son; Kazuoki Inoue; Minako Kamimoto; Shin‐ichi Taniguchi (Journal of General and Family Medicine)
Negative capability or tolerance for uncertainty is important for primary care physicians. The 2022 edition of the Model Core Curriculum for Medical Education also states that the content of professionalism is to “keep thinking about unanswerable questions.”